Pradhan Mantri Jan-Dhan Yojana: An Evaluation - T, Ravikumar (Ushus Journal of Business Management, 2018)
Financial inclusion is a process of providing access and usage of financial services like savings, credit, insurance and payment facilities by the financially excluded people. Initiatives towards financial Inclusion have been taken by the Government of India which includes priority lending, lead bank scheme, nationalisation of banks, Swabhimaan approach and Pradhan Mantri Jan Dhan Yojna (PMJDY). This article evaluates Pradhan Mantri Jan-Dhan Yojana scheme critically and its difference with a previous similar scheme.